Incentives and the delegation of decision making power in sovereign wealth funds - Artur Grigoryan (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2011)
The paper models the incentives of a politician to delegate the decision making power in a sovereign wealth fund to an independent external manager. It formalizes the learning-effects as well as the increase of transparency of the SWF and the rise of investment possibilities associated with higher transparency. It also focuses on the role of elections as a basic mechanism to control and discipline politicians. I show that the politician has incentives for strategic behaviour if voters have incomplete information about his competence. The paper also studies when the delegation of decision making power is socially optimal and under which circumstances it takes place.
Keywords: D7; E6; F3; G2; 330; Sovereign Wealth Fund (SWF); Transparency; Policy Delegation; External Management; Staatsfonds; Kooperative Führung; Public Choice; Ökonomischer Anreiz; Theorie